The Construction of Akhlak Values in the Movie “Cinta Laki-Laki Biasa” - Khadafi, Muhammad Umar; Rifai, Akhmad (Jurnal Ilmiah Syi'ar, 2023)
ncreasingly, visual media is becoming very interesting to research. Movie at this time continues to be a relevant medium in conveying ideas, cultural messages and life values to the community. The movieCinta Laki-Laki Biasais very interesting to be studied in more depth. In relation to the akhlak value contained in the use of symbols constructed in this movie. The purpose of this paper is to examine the construction of akhlak values to God and the construction of akhlakvalues to fellow humans in the movieCinta Laki-Laki Biasa. Data was collected by analyzing movie scenes using a qualitative descriptive approach. The analysis tool uses the framing model of Zhongdang Pan and Gerald M. Kosicki. This paper found that this movie provides the construction of akhlak values in a form that is very relevant to be interpreted by society. The results include akhlak construction to God in the form of using the Veil as a value of obedience and carrying out the command of worship under any circumstances and being manpaun. Construction of akhlak values to fellow humans in the form of a generous attitude and an attitude of honesty of Rafli character. Construction of akhlak values to the family in the form of maintaining and caring for the family and loving parents. All these values are framed in various symbols, images and specific situations that make up an interesting image scene. This paper is only limited to examining akhlak values in movies. It is hoped that further research can use semiotic analysis methods or other relevant methods and examine different problems.